OPTIMASI KOMPOSISI TWEEN 80 DAN SPAN 80 SEBAGAI EMULGATOR DALAM REPELAN MINYAK ATSIRI DAUN SERE (Cymbopogon citratus (DC) Stapf) TERHADAP NYAMUK Aedes aegypti BETINA PADA BASIS VANISHING CREAM DENGAN METODE SIMPLEX LATTICE DESIGN - Endah Nurlaela; Nining Sugihartini; Azis Ikhsanudin (Universitas Ahmad Dahlan, 2012)
The disease of Dengue hemorrhagic fever (DHF) is caused by the bite of femaleAedes aegypti mosquito. Cream of repelan sere leaf essential oils can be used to preventmosquito bites. The cream of volatile oil sere (Cymbopogon citratus (DC) Stapf)required emulsifier to maintain the stability of cream. Tween 80 and Span 80 is a widelyused emulsifier in a cream formula. Aims of this study is to determine the optimumcomposition of Tween 80 and Span 80 as emulsifier in a cream repelan of sere leafessential oils in the basis Vanishing Cream with Simplex Lattice Design methode. ThreeFormula cream is designed based on the Simplex Lattice Design methode with a ratio ofTween 80: Span 80 as follows: FI (100%-0%), F II (50%-50%), F III (0%-100%).Cream was then tested repelan activity and physical properties that includespreadibility, adhesivity and irritation. Data of physical properties and repellantactivity was calculate to get the optimum formula. The validity of optimization methodswas evaluated by comparing experimental results with predicted results in optimumcream formula with t test at 95% level of confidence. The results of study showed that theoptimum composition of Tween 80: Span 80 was 60%:40%. Cream with optimumemulsifier composition was predicted has spreadibility 29.24 cm2; adhesivity 3.512seconds; irritation 0.608; power repelan 41.469 minutes. T test results showed nosignificant differences between the experimental results and predicted results (p<0.05).